2013
DOI: 10.1186/1471-2164-14-224
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNA-mRNA functional interactions in UVB-induced senescence of human diploid fibroblasts

Abstract: BackgroundCellular senescence can be induced by a variety of extrinsic stimuli, and sustained exposure to sunlight is a key factor in photoaging of the skin. Accordingly, irradiation of skin fibroblasts by UVB light triggers cellular senescence, which is thought to contribute to extrinsic skin aging, although molecular mechanisms are incompletely understood. Here, we addressed molecular mechanisms underlying UVB induced senescence of human diploid fibroblasts.ResultsWe observed a parallel activation of the p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 72 publications
(90 reference statements)
2
45
0
Order By: Relevance
“…Noteworthy, all the studies done previously have been conducted using a single UV irradiation and we are the first one reporting the effect of chronic irradiation on human transcriptome. In our study, we have found that a CLUV treatment induces response to stress as described in previous study [66]. Indeed, our transcriptomic analysis found a deregulation in the ‘‘cell death”; “inflammatory response”; “response to wounding” and “response to stimulus” in the ‘‘response to stress” biological process.…”
Section: Discussionsupporting
confidence: 83%
“…Noteworthy, all the studies done previously have been conducted using a single UV irradiation and we are the first one reporting the effect of chronic irradiation on human transcriptome. In our study, we have found that a CLUV treatment induces response to stress as described in previous study [66]. Indeed, our transcriptomic analysis found a deregulation in the ‘‘cell death”; “inflammatory response”; “response to wounding” and “response to stimulus” in the ‘‘response to stress” biological process.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, the set of miRNAs with reduced expression during DGCR8-mediated arrest are also downregulated during oncogeneinduced senescence (Fig. 4A), replicative senescence (Bonifacio & Jarstfer, 2010;Marasa et al, 2010;Wang et al, 2011;Faraonio et al, 2012) or DNA-damage induced senescence (Greussing et al, 2013) in different strains of human primary fibroblasts. In addition, some of these miRNAs have been shown to bypass oncogene-induced senescence in human fibroblasts or epithelial cells (Voorhoeve et al, 2006;Borgdorff et al, 2010; and are overexpressed in tumors (Ivanovska et al, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…An alternative, noncanonical pathway leads to the generation of pre-miRNA molecules from splicing of intron-encoded precursors, mirtrons, without the participation of the Drosha-DGCR8 complex. pre-miRNAs are subsequently exported to cytoplasm where they are further processed by Dicer and loaded into the RNA-induced silencing complex (RISC) to produce destabilization and translational inhibition of target genes (Guo et al, 2010). Aberrant miRNA expression is a common trend of human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms underlying UVB induced senescence were investigated in human diploid fibroblasts [34]. Using genome-wide transcriptome analysis, a transcriptional signature of UVB-induced senescence was established.…”
Section: Micrornas and Uv-exposed Skinmentioning
confidence: 99%